Stimulation of gastrin release by bombesin and canine gastrin-releasing peptides. Studies with isolated canine G cells in primary culture. - Sugano, K (1987)
Bombesin, a polypeptide derived from frog skin, has been shown to stimulate gastrin release from the gastric antrum in vivo and in vitro. To elucidate the mechanisms of this effect, we developed a method to culture isolated and enriched G cells from canine stomach. After digestion of antral mucosa with collagenase and EDTA, dispersed cells were fractionated by counterflow elutriation then cultured on a collagen support. Bombesin and three molecular forms of canine gastrin-releasing peptides all stimulated gastrin release from G cells in a dose-dependent manner. The effect of bombesin was suppressed by somatostatin and potentiated by dibutyryl cyclic AMP (10(-3) M) but not by carbachol (10(-6) M). Extracellular calcium depletion attenuated the stimulation of gastrin release by bombesin but not by forskolin. These findings suggest that the bombesin family peptides directly activate G cells through calcium-dependent mechanisms to cause gastrin release.